A Case Study of Stakeholder Identification and Prioritization by Managers - Parent, Milena M. (Journal of business ethics, 2007)
The purpose of this article is to examine stakeholder identification and prioritization by managers using the power, legitimacy, and urgency framework of Mitchell et al. (Academy of Management Review 22, 853–886; 1997). We use a multi-method, comparative case study of two large-scale sporting event organizing committees, with a particular focus on interviews with managers at three hierarchical levels. We support the positive relationship between number of stakeholder attributes and perceived stakeholder salience. Managers’ hierarchical level and role have direct and moderating effects on stakeholder identification and perceived salience. We also found that most stakeholders were definitive, dominant, or dormant types – the other five types were rare. Power has the most important effect on salience, followed by urgency and legitimacy. Based on our case study, we offer several ways to advance the theory of stakeholder identification and salience.